2007
DOI: 10.1007/s00216-007-1783-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyvinyl resins used as binding media in paintings by pyrolysis–silylation–gas chromatography–mass spectrometry

Abstract: Polyvinyl resins, in particular poly(vinyl acetate) emulsions (PVA), are widely used in contemporary paintings as binding media, because of the optimum mechanical and optical properties these polymers confer on the paint layers. A study has been carried out to chemically characterize samples of PVA resins prepared as coating films from commercial products currently available from fine arts suppliers. For this purpose, a new method has been based on "on-line" silylation-pyrolysis using hexamethyldisilazane as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 12 publications
3
17
0
Order By: Relevance
“…At the same time, the suitability of pyrolysis-gas chromatographymass spectrometry (Py-GC-MS) as a complementary technique for evaluating biodeterioration processes was considered. For this purpose, a method based on the on-line derivatization of samples with hexamethyldisilazane (HMDS) was applied [16]. This method is based on the formation of trimethylsilyl ethers and esters, and has been proposed as an alternative to other commonly employed derivatization reagents such as tetramethyl ammonium hydroxide, to improve the detection of hydroxylated compounds and to avoid isomerization and unwanted alkylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the suitability of pyrolysis-gas chromatographymass spectrometry (Py-GC-MS) as a complementary technique for evaluating biodeterioration processes was considered. For this purpose, a method based on the on-line derivatization of samples with hexamethyldisilazane (HMDS) was applied [16]. This method is based on the formation of trimethylsilyl ethers and esters, and has been proposed as an alternative to other commonly employed derivatization reagents such as tetramethyl ammonium hydroxide, to improve the detection of hydroxylated compounds and to avoid isomerization and unwanted alkylation reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of ageing are fairly known and have been extensively reported, including increased brittleness, loss of tensile strength, darkening, yellowing and loss of translucency among others [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that Py-GC-MS can be successfully used to identify monomers and plasticizers used in acrylic and vinyl resin based products [1,3]. Alternatively, Domé nech et al have recently optimized an ''on-line'' derivatization method using hexamethyldisilazane (HMDS) as a derivatization reagent for the study of acrylic and vinyl resins as well as some of the additives present in different commercial formulations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations